Dynamic effects in friction and adhesion through cooperative rupture and formation of supramolecular bonds. Issue 17 (2nd April 2015) - Blass, Johanna; Albrecht, Marcel; Bozna, Bianca L.; Wenz, Gerhard; Bennewitz, Roland
Abstract : Friction and adhesion mediated by complexation of multiple adamantane connector molecules reveal a remarkably difference in their dynamic behavior. Abstract : We introduce a molecular toolkit for studying the dynamics in friction and adhesion from the single molecule level to effects of multivalency. As experimental model system we use supramolecular bonds established by the inclusion of ditopic adamantane connector molecules into two surface-bound cyclodextrin molecules, attached to a tip of an atomic force microscope (AFM) and to a flat silicon surface. The rupture force of a single bond does not depend on the pulling rate, indicating that the fast complexation kinetics of adamantane and cyclodextrin are probed in thermal equilibrium. In contrast, the pull-off force for a group of supramolecular bonds depends on the unloading rate revealing a non-equilibrium situation, an effect discussed as the combined action of multivalency and cantilever inertia effects. Friction forces exhibit a stick-slip characteristic which is explained by the cooperative rupture of groups of host–guest bonds and their rebinding. No dependence of friction on the sliding velocity has been observed in the accessible range of velocities due to fast rebinding and the negligible delay of cantilever response in AFM lateral force measurements.